2012
DOI: 10.1557/opl.2012.1589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Equivalent Sites on the Dynamics of Bimetallic Nanoparticles

Abstract: Using a Sutton and Chen interatomic potential, we study the molecular dynamics of AuPd nanoparticles with an initial icosahedral structure at different temperatures and concentrations, where each relative concentration of the 561-atom particles was made by placing atoms of the same species at equivalent sites, in order to identify under which conditions the melting transition temperature appears for each particle. In addition, we compute global order parameters in order to correlate the obtained results with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several nanoalloys have been studied either within a theoretical approach , or experimentally. , From the theoretical perspective, for example, the structural rearrangement of Au–Pd small clusters on a titania substrate has been investigated using MD under spin-polarized Kohn–Sham density functional theory (DFT) . The authors found that at finite temperature the Pd atoms migrated to the outer surface of the cluster, producing potential active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Several nanoalloys have been studied either within a theoretical approach , or experimentally. , From the theoretical perspective, for example, the structural rearrangement of Au–Pd small clusters on a titania substrate has been investigated using MD under spin-polarized Kohn–Sham density functional theory (DFT) . The authors found that at finite temperature the Pd atoms migrated to the outer surface of the cluster, producing potential active sites.…”
Section: Introductionmentioning
confidence: 99%